ANALISIS PERBEDAAN KESEJAHTERAAN ANTARA ANGGOTA DAN NON ANGGOTA BADAN USAHA MILIK DESA KARANG INDAH KECAMATAN MANDASTANA KABUPATEN BARITO KUALA - REGIE ZARATA; IKA CHANDRIYANTI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study was aimed to (1) know the welfare condition between member and non-member of BUMDes Karang Indah (2) know the strategies that can developing BUMDes to increase the welfare of Karang Indah villagers.Respondents of the study wetre 76 of the BUMDes member families and 34 of the BUMDes non-member families, which is their occupations as farmer, seller, and breeder in Karang Indah Village, Mandastana, Barito Kuala. The data were processed by independent sample t-test and SWOT analysis.            The results of the study showed the welfare condition between member and non-member of BUMDes were different and its measured by household income, household expenditure, household saving, education, and employment. These variables showed the non-member of BUMDes were more in welfare than member of BUMDes. The results of SWOT analysis were: (1) cooperating with bank to lend capital for villagers business; (2) creating productive bussiness unit; (3) keeping the stocks of goods; (4) doing sosialization about BUMDes frequently; (5) fixing the record system of BUMDes income.  Village government should fix the management of BUMDes, include strategic planning, recording system for BUMDes income, and strategies to develop BUMDes. They should do these to avoid the BUMDes existence as a trend and formality, but as a way to increase the villagers welfare condition, especially the member of BUMDes.                       Keywords: BUMDes, Welfare, Household Income, Household Expenditure, Household Saving, Education, Employment